Introduction of the principles of quality management system in educational institution; Australian Journal of Scientific Research; No.2. (6), July-December. Vol. III - Kvesko R. B. Raisa Bronislavovna; Kvesko S. B.; Hasanova V. V.; Kvesko S. E. (2014, 2014)
В фонде НТБ ТПУ отсутствует